ANÁLISE COMPARATIVA DE DUAS DIFERENTES ABORDAGENS NA SIMULAÇÃO DE PAREDES TROMBE NO ENERGYPLUS - Ziebell, Clarissa S.; Aymone, José L. F.; Cunha, Eduardo Grala (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The simulation of the thermal performance of buildings plays an important role in the correct architectural design. This paper is dedicated to the simulation of a passive air conditioning system: the Trombe wall. The goal is to evaluate the impact of using different ways to simulate Trombe walls in the EnergyPlus software. The results of a model where the Trombe wall is simulated through the ZoneThermalChimney object with another model using the AirflowNetwork group are compared. As a result, it was found that there were no significant differences in the mean hourly temperatures obtained for the two simulated models, which was on average equal to 0.37 °C.